India – a Potential Major Non-NATO Ally - Olga A. Bazhenova (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2022)
Introduction. Allied relations between India and United States were based during Barack Obama administration and were further developed with Donald Trump coming to power. The interplay that has intensified between states in recent years can contribute to the creation of a new geopolitical space – the Indo-Pacific region. Trade in arms and military equipment is the catalyst for cooperation and the major non-NATO ally status can create all favorable conditions for thus cooperation. United States and India rapprochement, caused, in particular, by geopolitical situation in the Asia-Pacific and the change of power in United States, has led to the emergence of discussions in the American political society about assigning India major non-NATO ally status. Seventeen states in various regions of the world already own this status.